Neural substrates of child irritability in typically developing and psychiatric populations. (August 2015) - Perlman, Susan B.; Jones, Brianna M.; Wakschlag, Lauren S.; Axelson, David; Birmaher, Boris; Phillips, Mary L.
Highlights: This study compared children (ages 6–9) with clinically high irritability to healthy children. A novel and child-friendly task induced frustration during fMRI scanning. Results indicated differential activation of the ACC and PCC in clinical children. Activation in the ACC and striatum during frustration varied dimensionally with irritability. Results indicate deviation in reward and emotional function in irritable children. Abstract: Irritability is an aspect of the negative affectivity domain of temperament, but in severe and dysregulated forms is a symptom of a range of psychopathologies. Better understanding of the neural underpinnings of irritability, outside the context of specific disorders, can help to understand normative variation but also characterize its clinical salience in psychopathology diagnosis. This study assessed brain activation during reward and frustration, domains of behavioral deficits in childhood irritability. Children (age 6–9) presenting in mental health clinics for extreme and impairing irritability ( n  = 26) were compared to healthy children ( n  = 28). Using developmentally sensitive methods, neural activation was measured via a negative mood induction paradigm during fMRI scanning. The clinical group displayed more activation of the anterior cingulate and middle frontal gyrus during reward, but less activation during frustration, than healthy comparison children. The opposite pattern was found in the posterior cingulate. Further, in clinical subjects, parent report of irritability was dimensionally related to decreased activation of the anterior cingulate and striatum during frustration. The results of this study indicate neural dysfunction within brain regions related to reward processing, error monitoring, and emotion regulation underlying clinically impairing irritability. Results are discussed in the context of a growing field of neuroimaging research investigating irritable children.